A Hybrid DDM Algorithm Based on Weight Function - Guisheng Zhang; Xia Zhang; Deyu Li (FSKD 2008 : Fifth International Conference on Fuzzy Systems and Knowledge Discovery : 18-20 October, 2008 : Jinan, Shandong, China : proceedings, 2008)
The high level architecture (HLA) has become the focus of distributed interactive simulation's general technology frame. Data distribution management (DDM), one of the six services in run time infrastructure (RTI), provides data filtering mechanism to meet the requirements of system scalability. This paper describes and reviews the popular DDM filtering algorithms, and discusses their respective merits. Especially, it presents a new hybrid DDM algorithm which is based on weight function. Simulation experiments show this algorithm has some desirable theoretical properties. Comparing with the traditional DDM filtering algorithms, the presented approach can greatly improve the data filtering efficiency. It has achieved the goal of improving DDM performance.